Estudio del movimiento de arrancada en Halterofilia durante ciclos de repeticiones de alta intensidad mediante análisis cinemáticos - Campos, J.; Poletaev, P.; Cuesta, A.; Pablos,C.; Tebar, J. (European Journal of Human Movement, 2004)
Power capacity is one of the keys to optimizing athletic performance. In weihtllifting, it is necessary to train the atlete to generate the maximum muscular force at the most higher speed. The purpose of study was to describe the kinematic characteristics of the snatch technique of the individual pattern of elite spanish weightlifter during different sets of high intensity repetitions (90% of 1RM). Two syncronized s-VHS cameras operating at 50 fields were used to record the lifts. Correlation analysis coefficient of variation was used to compare the selected variables. Results revealed that the mayority the variables, except vertical acceleration of the bar and lost of height during drop under the barbell, show a low index of variability (CV: 1 to 6 %). Furthemore, it was observed that stability is bigger in sets with less barbell mass. For the future, it is proposed to applied the same methodology to 3, 4 and 5RM.